The Transition From Ambrisentan to Macitentan in Patients With Pulmonary Arterial Hypertension: A Real-word Prospective Study - Chen, Yusi; Luo, Jun; Chen, Jingyuan; Kotlyar, Eugene; Li, Zilu; Chen, Wenjie; Li, Jiang (Frontiers in Pharmacology, 2022)
Background: In a long-term event-driven trial, macitentan has demonstrated beneficial time to clinical worsening in patients with pulmonary arterial hypertension (PAH) and reduced PAH-related hospitalization rates compared with placebo. Macitentan is the most recently approved endothelin receptor antagonist (ERA) and is the first ERA that has shown efficacy for morbidity and mortality in PAH patients; therefore, patients and physicians may consider converting treatment from ambrisentan to macitentan. Our study evaluated the safety, efficacy, and quality of life in PAH patients transitioning from ambrisentan to macitentan. Methods: This was a real-world, prospective study with a 12-month follow-up. PAH patients who had received stable doses of ambrisentan for over 3 months, were within the World Health Organization Functional Class II/III, and 6-minute walk distance ≥ of 250 meters were enrolled. The study included a screening period, followed by a transition phase, after which patients entered the long-term follow-up. Clinical data and treatment satisfaction outcomes were collected to assess and monitor the safety and efficacy of the transition. The trial was registered at the Chinese Clinical Trial Registry (www.chictr.org.cn; No. ChiCTR2000034898). Results: One hundred and fifty-seven enrolled PAH patients completed the transition. All criteria for continuous treatment transition were met by 145 patients (92.4%). Results showed improvements in exercise capacity, cardiac function, and hemodynamics compared with baseline. During the process, 4 patients discontinued macitentan due to adverse events. There was no statistical difference in the overall incidence of adverse events before and after the transition. Conclusion: Transition to macitentan from ambrisentan was successful and well-tolerated by PAH patients, and was associated with greater efficacy and satisfaction.